An Analysis of English-Speaking Anxiety Awareness among Vocational High School Students - Elisa Ayu Maharani (Universitas Negeri Surabaya, 2026)
Anxiety related to speaking in English is one of the major problems encountered by vocational high school learners, which might affect their communicative skills and self-reassurance in the classroom. The research focuses on identifying students’ awareness of speaking anxiety and the factors leading to it. A mixed method approach was utilized through the survey, where 145 students filled out the Foreign Language Classroom Anxiety Scale (FLCAS), and the interviews with 16 students were conducted. Quantitative data shows that most of the students suffer from moderate and high anxiety. Thematic analysis revealed seven main categories, namely nervousness when speaking in front of people, fear of mistakes, lack of self-confidence, anxiety from peer evaluation, small vocabulary, sudden calling upon, and students’ coping technique. These findings emphasize the importance of metacognitive and emotional awareness, also suggest the implication of pedagogical for teachers in building a more supportive classroom environment.